The efficacy of negative pressure wound therapy for diabetic foot ulcers: A systematised review. Issue 3 (August 2019) - Wynn, Matthew; Freeman, Samantha
Abstract: Aim: This review investigated the current state of knowledge on negative pressure wound therapy (NPWT) used to treat diabetic foot ulceration (DFU), its clinical effectiveness and any current issues in the research. NICE have recommended research into the clinical effectiveness of different dressing types for DFUs since 2015. Methods: A systematic search of the British Nursing Index, CINAHL, Cochrane Central and PubMed was undertaken. Only primary studies were included and studies investigating a combination of NPWT and other therapies were excluded. All the included studies were published in English between 2008 and 2018 and were peer reviewed. Results: The search yielded seven studies for inclusion in the qualitative analysis. The studies included a variety of methodologies specifically; 3 randomized controlled trials, 2 case series', 1 non-controlled trial and 1 randomized case-control study. Three main themes were identified and formed the focus of the qualitative synthesis. Discussion: All the included studies reported that NPWT led to better clinical outcomes when compared to standard treatment. However, the studies had numerous methodological flaws such as the absence of validated tools for the measurement of outcomes such as wound area and depth; a lack of statistical power calculations to determine adequate sample sizes or the significance of outcome measures. Additionally, there was little consistency in the pressures used for the NPWT devices. Finally, many of the controlled trials did not conform to the standard of reporting trials stipulated by the CONSORT statement.